LANDASAN BIMBINGAN DAN KONSELING DALAM MENGHADAPI BERBAGAI LINTAS BUDAYA - Agus Basuki (Paradigma, 2013)
Abstract. Guidance and counseling is an integral part of the education that have objects of human behavior. Human behavior in the context of social interaction can never be separated from the social environment that involves the various components. One such component is the culture. Students are highly influenced by the culture of the parents, preschool, and school vary greatly in terms of the extent to which the children are encouraged to develop long-term relationships with peers and teachers outside the family.Various elements in the areas of people's lives is the seeds that could enrich the culture to build a strong community, but instead can weaken the strength of the nation with various squabbles and disputes. Therefore the social relations necessary to arrange to run centripetal, disagreements, disputes must be addressed not by dogmatic attitude but with rational critical attitude. Rational critical attitude can be done through education, because education is a strategic component which has an important role in determining the forward movement of the nation